Redesain Metode Kerja Guna Reduksi Workload Fisik Dan Mental Pekerja Di Pt. Spu Palembang - Setiawan, Heri; Kusmindari, Christofora Desi (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2020)
PT. SPU Palembang is an industrial company that produces Hospital Furniture and Rehabilitation products with the trademark SHIMA. This study aims to reduce the physical and mental workload received by workers in the Machine Shop Department. This research is focused on the production process .Measurement of physical workload uses the calculation of the worker's heart rate by calculating the percentage of Cardiovascular Load (CVL). Measurement of mental workload using the National Aeronautics and Space Administration Task Load Index (NASA-TLX) score calculation method. The results obtained based on the aspect of NASA-TLX before the proposal almost all workers receive a mental workload with a value of > 80 that is included in the category of heavy mental workloads except Milling-Drilling Workers (4) have a score < 80 in the category of moderate mental workload. After the proposal all workers have a score < 80 so that the mental workload received falls into the medium category. Based on the proposals applied to the Lathe Worker (1) and the Milling-Drilling Worker (4) namely the improvement of work methods in the process of turning, punching, and the proposed holding of a reminder as a tool to remember, the results obtained %CVL from both workers < 30%. Three other workers, although experiencing a decline, remained at > 30%. The category of mental workload received by workers from previously included in the category of heavy mental workload dropped to moderate